AMMONIUM CONTENT OF BIOTITES FROM GRANITIC AND METAMORPHIC ROCKS IN THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - タイノショウ, ヨシアキ; タカハシ, ユウヘイ; オサナイ, ヤスヒト; ツチヤ, ノリヨシ; TAINOSHO, Yoshiaki; TAKAHASHI, Yuhei; OSANAI, Yasuhito; TSUCHIYA, Noriyoshi (National Institute of Polar Research, 1991)
P(論文) Ammonium content of biotites from granitic and metamorphic rocks in the Sør Rondane Mountains in East Antarctica has been determined in order to examine the difference in the NH_4^+ content of biotites among six granite types. Ammonium content of biotites ranges from 12 to 23ppm (average, 18ppm) in the migmatitic granite, 23 to 80ppm in the foliated granite (average, 46ppm), 22 to 86ppm (average, 66ppm) in the massive granite with migmatitic margin, 11 to 66ppm (average, 42ppm) in the discordant granite, 28 to 106ppm (average, 67ppm) in the granite sheet and dyke, 76 to 109ppm (average, 92ppm) in the small granodiorite bodies, and 25 to 142 ppm (average, 52ppm) in the metamorphic rocks. High NH_4^+ content found in biotites from the small granodiorite bodies is probably due to a result of the interaction between the granitic magma and surrounding metamorphic rocks. Biotites from the migmatitic granite have lowest NH_4^+ content in granitic rocks analyzed. The fact is in discord with the field evidence. The very low NH_4^+ content in biotite from the Nils Larsen tonalite is in good accordance with the view postulated from petrochemical data that granitic magma of this tonalite was directly derived from the melting of subducted oceanic crust or the overlying mantle. In metamorphic rocks, the low NH_4^+ content in biotites is probably due to liberation of NH_4^+ from the rocks during high grade metamorphism (granulite facies). departmental bulletin paper